SleepWeb : uma plataforma web para suporte no monitoramento e avaliação de qualidade de sono - Hernandes, Matheus Rigoni (2020)
The sleep is physiologic state, fundamental for human health, and responsible for regeneration of the nervous system and human organism. The growing number of diseases related with poor sleep quality, has brought importance to sleep monitoring. Currently, the polysomnography is the gold standard for sleep monitoring. This technique demands that the patient stays for sleep session under supervision of a team of nurses or doctors, and connected to several sensors. This invasive scenario makes the polysomnography uncomfortable and hard to long-term sleep monitoring. Looking for alternatives for polysomnography, researchers from biomedical engineering fields have been working on development of new techniques for monitoring sleep. Techniques less invasive and capable to conduce remote and long-term exams. However, most of these alternative monitoring techniques lacks of support system, to help doctors and researchers to conduct studies and exams. Aiming to offer a solution for this problem, comes the main goal of this project, the specification and development of an environment to support sleep monitoring, called SleepWeb. Through the SleepWeb, doctors and researchers are able to conduce exams, with different alternative sleep monitoring techniques, and qualify it results. The main goal of this project was the development of and environment, that offers dynamic and expansive structure, capable to be distributed across different locations and institutions, and also able to work with different types of hardware and software. During the research, theoretical components was researched, aiming to support the project, and also alternative sleep monitoring techniques, able to be integrated with the environment. When finished, the project was tested and simulated, with integration with two conceptual monitoring systems, one of then based in parallel project in development. Also, as contribution from this project, comes the index of sleep disturb detection. A proposal to standardize sleep monitoring results in a simple value, based on collect of multiple sleep quality indicators.